2-Aminoimidazoles as potent inhibitors of contaminating brewery biofilms. Issue 1 (12th January 2021) - Jacobs, Lene; Meesters, Jolien; Parijs, Ilse; Hooyberghs, Geert; Van der Eycken, Erik V.; Lories, Bram; Steenackers, Hans P.
Abstract: Cleaning and disinfection protocols are not always able to remove biofilm microbes present in breweries, indicating that novel anti-biofilm strategies are needed. The preventive activities of three in-house synthesized members of the 2-aminoimidazole class of anti-biofilm molecules were studied against 17 natural brewery biofilms and benchmarked against 18 known inhibitors. Two 2-aminoimidazoles belonged to the top six inhibitors, which were retested against 12 defined brewery biofilm models. For the three best inhibitors, tannic acid (n° 1), 2-aminoimidazole imi-AAC-5 (n° 2), and baicalein (n° 3), the effect on the microbial metabolic activity was evaluated. Here, the top three inhibitors showed similar effectiveness, with baicalein possessing a slightly higher efficacy. Even though the 2-aminoimidazole was the second-best inhibitor, it showed a lower biocidal activity than tannic acid, making it less prone to resistance evolution. Overall, this study supports the potential of 2-aminoimidazoles as a preventive anti-biofilm strategy.